Predikcija - prognoza uspjeha na parteru na osnovu morfoloških karakteristika - Tabakovic, M.; Hadzikadunic, A.; Turkovic, S.; Novakovic, R. (Sportski Logos, 2014)
Prediction of success on the floor based on morphological characteristics was performed on selected sample of 180 male respondents, aged 16 to 18. All subjects were students of "Sportska gimnazija" in Sarajevo. In this reserach, a set of predictor variables for assessment of the morphological characteristics represents a group of four (4) isolated latent morphological dimensions. The criteria model of variables that assess the efficiency of performing an artistic gymnastics floor routine consists of a group of eleven elements, where the isolated criterion from the above mentioned system of variables contains the largest amount of information from the system and is called (THE FLOOR). Presented values of the parameters of a regression analysis of the criterion variable (THE FLOOR) in the latent space of morphological variables, the number of valid partial regression coefficients, i.e. the three latent dimensions have a statistically significant impact on the criterion variable, it leads us to the following conclusion. Prediction (prognosis) impact prediction system of morphological variables on the criterion variable (THE FLOOR), can be made with more confidence with the help of the whole system of predictor variables, in relation to the reliability that can be done with the help of the obtained partial regression coefficients (BETA), i.e. the individual impact predictor variables on the criterion. Prediction system of variables explains (R Sguare) 27% of common variability with the criteria while the connection of the entire prediction system of variables with the criteria i.e. coefficients of multiple correlation equals (RO) 51, which represents the true relevant value. This correlation is significant on the level (Sig) .00. The second latent dimension (FAK-2) has the greatest influence on the criterion variable (THE FLOOR), which has been defined as a factor of longitudinal skeleton dimensionality (Beta)-46, next is the influence of the first isolated latent dimension (FAK-1) which has been defined as the factor of subcutaneous adipose tissue (Beta) -38 and finally the fourth isolated latent dimension (FAK-4) that has been defined as a factor of skeletal transverse dimensionality (Beta) -176, which is significant on the level (Sig) = ili < .05. The third isolated latent dimension (FAK-3) that has been defined as a voluminosity and body mass factor has no statistically significant influence on the criterion variable (THE FLOOR). All three isolated latent dimensions that have statistically significant influence on the criterion variable (THE FLOOR) have been negatively oriented, meaning they have a negative influence on the criterion variable. We can conclude that greater degree of longitudinal skeleton dimensionality, subcutaneous adipose tissue and skeletal transverse dimensionality have been limiting factors in the performance of the elements on the floor, i.e. the subjects with greater degree of the above mentioned morphological characteristics have had poorer performance of the elements of artistic gymnastics floor routine.